2021
DOI: 10.1093/advances/nmaa106
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Systematic Review of the Effects of Naringenin, a Citrus-Derived Flavonoid, on Risk Factors for Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of liver dysfunction worldwide. Recently, some natural compounds have attracted growing interest in the treatment of NAFLD. In this context, most attention has been paid to natural products derived from fruits, vegetables, and medicinal herbs. Naringenin, a natural flavanone, has been revealed to have pharmacological effects in the treatment of obesity and associated metabolic disorders such as NAFLD. The aim of this study was to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 94 publications
2
29
0
3
Order By: Relevance
“…Thus, the relative bioavailability of NAR was higher than quercetin and hesperetin. Most studies of NAR’s effects for NAFLD on animal models were conducted in large doses (50–100 mg/kg) and (or) in a long time (4–12 weeks) ( Naeini et al, 2020 ). Wang et al reported that NAR attenuated hepatic lipid accumulation and inflammation in methionine and choline deficient diet-induced NAFLD mice at 100 mg/kg for 7 days ( Wang Q. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relative bioavailability of NAR was higher than quercetin and hesperetin. Most studies of NAR’s effects for NAFLD on animal models were conducted in large doses (50–100 mg/kg) and (or) in a long time (4–12 weeks) ( Naeini et al, 2020 ). Wang et al reported that NAR attenuated hepatic lipid accumulation and inflammation in methionine and choline deficient diet-induced NAFLD mice at 100 mg/kg for 7 days ( Wang Q. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…NAR is abundant in a lot of fruits, vegetables, and nuts, such as lemon, grapefruit, oranges, and tomatoes. NAR has been reported to modulate several biological processes related to NAFLD including energy balance, lipid and glucose metabolism, inflammation, and oxidative stress ( Naeini et al, 2020 ). However, whether or not NAR attenuates NAFLD by activating adenosine 5′-monophosphate (AMP)-activated protein (AMPK), the key regulator in energy balance, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin (4, 5, 7-trihydroxyflavanone) is a flavonoid derived from grapes and citrus, which has recently shown positive effects on the respiratory system [ 15 ]. This flavonoid has also been proven to possess various pharmacological properties such as anticancer, antimutation, and antiatherogenic [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial clinical studies have demonstrated that naringenin possesses preventive effects against NAFLD and its related complications by ameliorating obesity, insulin resistance, hepatic steatosis, and liver fibrosis through attenuation of oxidative stress, inflammation, and profibrogenic pathways, as well as regulation of energy homeostasis and lipid metabolism [21]. Additionally, a large number of experimental models found a meaningful decline in the serum levels of bilirubin and hepatic enzymes including aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and lactate dehydrogenase by naringenin treatment [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%